Evaluation of the Impact of the MBG Socio-Economic Program on Household Food Security - sugiharto sugiharto; Qimyatussa'adah Qimyatussa'adah; Hedi Pandowo (Journal of Social Science and Humanities, 2026)
Food security is a fundamental pillar of sustainable development, enshrined in Sustainable Development Goal 2 (Zero Hunger). The Free Nutritious Meals Program (MBG) represents a strategic intervention by the Indonesian government to improve nutritious food access for vulnerable groups, including pregnant women, toddlers, school-age children, and the elderly. This study evaluates the socio-economic impact of the MBG program on household food security using a quasi-experimental design combining Propensity Score Matching (PSM) and Difference-in-Differences (DID) methods. A stratified random sample of 844 respondents was selected, comprising 422 MBG recipient households (treatment group) and 422 non-recipient households (control group). Results demonstrate that the MBG Program significantly reduced the Household Food Insecurity Access Scale (HFIAS) score by 4.3 points (p<0.01), equivalent to a 35.8% reduction in food insecurity, increased the Dietary Diversity Score (DDS) by 2.3 food groups (p<0.001), and raised the Food Consumption Score (FCS) by 18.2 points (p<0.001). Economic impacts included monthly food expenditure savings of IDR 473,000 and a reduction in the food expenditure share from 59.3% to 45.8%. Social impacts encompassed a 19.2-point improvement in nutrition knowledge and enhanced health service utilization. The program demonstrated greater effectiveness among low-income households, rural populations, and female-headed households, with participation duration and implementation quality as key effectiveness determinants.